Pengaruh Work Life Balance Terhadap Job Satisfaction Melalui Employee Engagement - Khoiro, Muhibbatul; Frianto, Agus (Jurnal Ilmu Manajemen, 2024)
PT. Pos Indonesia (Persero) Mojokerto Office is a state-owned company that operates in the income, transmission, collection, sorting, and delivery of letters or postal packages. The post office also conducts sales of postal objects such as philately, for example, stamps, envelopes, postcards, and package wrapping equipment. In some countries, post offices accept applications for passports, postal orders, money orders, ordering goods, selling insurance, postal giro services and banking & services. This study aimed to test and analyse the effect of work-life balance on job satisfaction through employee engagement at PT. Pos Indonesia (Persero) Mojokerto Office. This research uses a quantitative approach. The sampling technique used non-probability sampling with a saturated sample type, where all population members were sampled with a total of 36 PT respondents. Pos Indonesia (Persero) Mojokerto Office. The statistical analysis used in this research is partial least squares (PLS) with the help of SmartPLS 4.0.9.6 software. The results of this study explain that work-life balance has a significant positive effect on job satisfaction, work-life balance has a significant positive effect on employee engagement, employee engagement has a significant positive impact on job satisfaction, employee engagement does not successfully mediate the relationship between work-life balance and job satisfaction.